2016
DOI: 10.3109/13651501.2016.1144771
|View full text |Cite
|
Sign up to set email alerts
|

Possible relationship between amino acids, aggression and psychopathy

Abstract: Our study showed a relationship between serum amino acid levels and the scores of aggression and psychopathy. We think that this is a productive research area for understanding the relationship among biochemical factors, aggression and psychopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
5
7
0
6
Order By: Relevance
“…Our results are consistent with results obtained for other psychiatric disorders, so have lower serum L-arginine levels been associated with antisocial personality disorder (APD) and schizophrenia (50,51).…”
Section: Serotonergic Dopaminergic and Gabaergic Pathways And Childsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with results obtained for other psychiatric disorders, so have lower serum L-arginine levels been associated with antisocial personality disorder (APD) and schizophrenia (50,51).…”
Section: Serotonergic Dopaminergic and Gabaergic Pathways And Childsupporting
confidence: 92%
“…We found L-aspartic acid, which is involved in gluconeogenesis to differ significantly between twins scoring high on aggression as compared to their low scoring co-twins in the withinfamily replication analyses. While we reported lower urinary Laspartic acid levels in twins with high aggression, a previous study reported increased serum levels in patients with APD (50). Congruent with our findings, lower plasma levels of Laspartic acid were reported in MDD patients as compared to controls (56).…”
Section: Energy Metabolism and Childhood Aggressionsupporting
confidence: 85%
See 1 more Smart Citation
“…Associations between lipid concentrations and aggression have previously been noted [4,[10][11][12][13], while other low-molecular-weight molecules might hold more promise for novel findings. Amino acids and ketone bodies (low-molecularweight molecules categorized in NMR) have been associated with emotional and behavioral problems other than aggression [14][15][16][17], and some studies have shown amino acids and similar molecules associated with anger and psychopathy [18], schizophrenia-related violence [13], and childhood aggression [19]. Accordingly, these areas offered a reasonable place to focus our exploratory investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Глутамат (глутаминовая кислота) является основным возбуждающим нейротрансмиттером в головном мозге. Глутамат сыворотки превращается в гамма-аминомасляную кислоту (ГАМК) после прохождения гематоэнцефалического барьера, в результате чего высокий уровень глутамата в сыворотке может повышать концентрацию ГАМК в ЦНС [25]. При этом нейромедиаторная функция глутаматергической системы в большой мере определяется взаимодействием глутамата с глутаматными рецепторами (GluR), которые широко представлены в различных структурах мозга и подразделяются на метаботропные (mGluR) и ионотропные (iGluR) [26].…”
unclassified